The Location of the Fibular Tunnel for Anatomically Accurate Reconstruction of the Lateral Ankle Ligament: A Cadaveric Study. (19th March 2021) - Park, Jeong-Hyun; Kwon, Hyung-Wook; Kim, Digud; Park, Kwang-Rak; Lee, Mijeong; Choi, Yu-Jin; Cho, Jaeho
Abstract : We aimed to describe the location of fibular footprint of each anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL), as well as their common origin in relation to bony landmarks of the fibula in order to determine the location of the fibular tunnel. In 105 ankle specimens, the center of the footprints of the ATFL and CFL (cATFL and cCFL, respectively) and the intersection point of their origin (intATFL-CFL) were investigated, and the distances from selected bony landmarks (the articular tip (AT) and the inferior tip (IT) of the fibula) were measured. Forty-two (40%) specimens had single-bundle ATFL, and 63 (60%) had double-bundle patterns. The distance between intATFL-CFL and IT was 12.0 ± 2.5 mm, and a significant difference was observed between the two groups (p = 0.001 ). Moreover, the ratio of the intATFL-CFL location based on the anterior fibular border for all cadavers was 0.386. The present study suggests a reference ratio that can help surgeons locate the fibular tunnel for a more anatomically accurate reconstruction of the lateral ankle ligament. Also, it may be necessary to make a difference in the location of the fibular tunnel according to the number of ATFL bundles during surgery.